Growth Pattern of Body Size in Baduy People - Eneng Nunuz Rohmatullayaly; Alex Hartana; Yuzuru Hamada; Bambang Suryobroto (Bogor Agricultural University, Indonesia, 2017)
Understanding body size growth pattern is one of the best ways to find out biological variation in phenotypic plasticity, health and nutritional statuses, and quality of life. Optimum environment and better nutrition are associated with rapid growth, tall stature, and early puberty. However, poor living condition impacts every stage of development, which results in variation in growth rates, growth periods, and body sizes across populations. Baduy is one of traditional populations who inhabit mountainous area in Kanekes Village, Lebak Regency, Banten Province, Indonesia. The traditional obligatory duties and taboos resulted in genetic, geographic, and cultural isolations. This leads to question whether the biocultural condition affects the growth pattern of their body size. We measured the body height, weight, and mass index of 340 girls and 239 boys aged 4–30 years sampled from 39 of 61 hamlets using cross-sectional method. We found that Baduy people had prolonged growth resulting in small body size because of slow rate and low spurt. This might be a selection to save body maintenance costs in biocultural condition with poor nutrition and high physical activity.